2021
DOI: 10.18186/thermal.1027435
|View full text |Cite
|
Sign up to set email alerts
|

Drop-in and retrofit refrigerants as replacement possibilities of R134a in domestic/commercial refrigeration and automobile air conditioner applications

Abstract: According to the EU F-gas Regulation, the phase-out of the high global warming potential (GWP) refrigerants (with higher than 150 GWP value) had been established. The most currently existing household and commercial refrigerators and automobile air conditioners applications based on single-stage vapour compression systems operate with R134a as working fluid. The present paper aims, to review and evaluate the performance of a set of eco-friendly alternatives refrigerants to replace R134a, without change or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The ratio of COP of the system under consideration to COP of the system operated reversibly (Carnot COP) is known as energetic efficiency, ... (7) Exergy destruction ratio (EDR) is ratio of irreversibility associated with a component to the exergy of fuel supplied. 10 ... (8) The efficiency defect (δ i ) is an indicator that gives the information about the fraction of energy (input) destroyed in a specific component so that one can find the component which performs worst in the system.…”
Section: (6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of COP of the system under consideration to COP of the system operated reversibly (Carnot COP) is known as energetic efficiency, ... (7) Exergy destruction ratio (EDR) is ratio of irreversibility associated with a component to the exergy of fuel supplied. 10 ... (8) The efficiency defect (δ i ) is an indicator that gives the information about the fraction of energy (input) destroyed in a specific component so that one can find the component which performs worst in the system.…”
Section: (6)mentioning
confidence: 99%
“…Refrigerator freezers and air conditioners were shown to be responsible for 21% and 12% of total exergy loss, respectively. HMOOD et al 8 reported that R1234yf could be a better drop in alternative to high GWP refrigerant R134a. Tarish et al 9 perform the exergy analysis using R161 operated in split air conditioner to find an alternative to R134a and R22 in different Iraq climate and find that the exergy efficiency of R161 operated system is 8.6% and COP is 7.3% higher than the R134a and R22 operated systems.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated refrigerants, especially chlorofluorocarbons (CFCs) and hydrochloroflurocarbons (HCFC), are the commonly used refrigerants in vapour compression refrigeration systems over the past century, Because of their outstanding thermodynamic and thermo-physical qualities. However, they possess poor environmental qualities due to their undesirable contributions to the ozone layer destruction and climate change by reason of their high global warming potential (GWP) (Hmood et al, 2021). In 1987, Montreal Protocol regulated the use of both the partially and fully halogenated chemicals including hydro-chlorofluorocarbons (HCFCs) and CFCs in air-conditioning and refrigeration systems as a result of their high ozone depletion potential (ODP) (Bolaji, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The refrigerant mass charge of R290/R600a was nearly 50%, with refrigeration effect higher by 35.29 percent and 12.5 percent, compressor operation lower by 9.12 percent and 14.68 percent, COP larger by 46.92 percent and 31.91 percent, and discharge compressor temperature lower by 8K and 5K than R134a, respectively. R134a/R1234yf (10:90, by weight) was used in an experimental study by Hmood et al [12] to replace R134a in a refrigerator. The electrical energy consumption was reduced by 7.5 percent, and the pull-down time was reduced by 14 percent in the binary mixture R134a/R1234yf.…”
Section: Introductionmentioning
confidence: 99%